The Influence Of Knowledge Sharing And Innovative Behavior On Team Innovation In Microfinance Institutions - Muhammad Ras Muis; Toman Sony Tambunan (Jurnal Manajemen Bisnis Eka Prasetya, 2024)
Team innovation in microfinance institutions lies in the quality of human resources. The rapidly changing times that occur must be able to be anticipated with quality innovation. The quality of human resources can be seen from the ability of employees to share knowledge and behave innovatively and can be assessed from the team innovation that occurs in the institution or organization. The population of this research is employees who work in the microfinance industry with a population of 2100. A sample of 300 employees was taken using the proportional stratified random sampling method. The data collection technique is by distributing questionnaires to all respondents. The data analysis method used is SEM (Structural Equation Modeling), with the Smart PLS program. This team's innovation concept will provide insight and guidance for employees to be able to increase the competitiveness and existence of Microfinance Institutions now and in the future.